2013
DOI: 10.1111/cdev.12053
|View full text |Cite
|
Sign up to set email alerts
|

Visual Attention to Global and Local Stimulus Properties in 6‐Month‐Old Infants: Individual Differences and Event‐Related Potentials

Abstract: Event-related potentials (ERPs) were utilized in an investigation of 21 six-month-olds' attention to and processing of global and local properties of hierarchical patterns. Overall, infants demonstrated an advantage for processing the overall configuration (i.e., global properties) of local features of hierarchical patterns; however, processing advantages were found to vary based on individual differences in look duration. Short-looking infants showed differences in the negative central ERP component and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 75 publications
2
30
0
Order By: Relevance
“…For example, systematic research on infant looking styles has demonstrated that infants who, on average, make shorter glances to novel stimuli both process information more rapidly, and typically encode global features rather than local features (Colombo, Freeseman, Coldren & Frick, 1995;Guy, Reynolds & Zhang, 2013).…”
Section: Processing Speedmentioning
confidence: 99%
“…For example, systematic research on infant looking styles has demonstrated that infants who, on average, make shorter glances to novel stimuli both process information more rapidly, and typically encode global features rather than local features (Colombo, Freeseman, Coldren & Frick, 1995;Guy, Reynolds & Zhang, 2013).…”
Section: Processing Speedmentioning
confidence: 99%
“…A significant reduction in the amplitude of the LSW has been routinely observed across repeated stimulus presentations. Thus, the LSW is believed to be associated with stimulus encoding and infant recognition memory (de Haan & Nelson, ; Guy, Reynolds, Mosteller, & Dixon, ; Guy, Reynolds, & Zhang, ; Nelson & Collins, , ; Reynolds, Guy, & Zhang, ; Snyder, ; Snyder, Webb, & Nelson, ; Webb et al., ; Wiebe et al., ).…”
Section: Preferential Looking Measures Of Infant Visual Attention Andmentioning
confidence: 99%
“…To explore this possibility, Guy, Reynolds, & Zhang (2013) utilized hierarchical patterns to examine global and local processing in 6-month-olds. Short- and long-looking infants were familiarized with a hierarchical pattern.…”
Section: Neural Measures Of Visual Attention and Object Recognition Imentioning
confidence: 99%
“…The global-precedence effect is characteristic of a mature and efficient visual processing strategy (Kimchi, 1992), and these differences in processing strategy would explain the long-lookers inability to fully process the more complex objects used as stimuli by Reynolds and colleagues (2011). Although these two sets of findings (Guy et al, 2013; Reynolds et al, 2011) indicate that an infant’s attentional style influences early recognition memory, because infants in these studies were familiarized with the repeated stimulus in a familiarization phase prior to the ERP testing the findings do not provide insight into exactly how attention influences stimulus encoding and subsequent recognition memory.…”
Section: Neural Measures Of Visual Attention and Object Recognition Imentioning
confidence: 99%
See 1 more Smart Citation